Efficient Double- and Triple-Junction Nonfullerene Organic Photovoltaics and Design Guidelines for Optimal Cell Performance - Firdaus, Yuliar; Ho, Carr Hoi Yi; Lin, Yuanbao; Yengel, Emre; Le Corre, Vincent M; Nugraha, Mohamad I; Yarali, Emre; So, Franky; Anthopoulos, Thomas D (ACS energy letters, 2020)
The performance of multijunction devices lags behind single-junction organic photovoltaics (OPVs) mainly because of the lack of suitable subcells. Here, we attempt to address this bottleneck and demonstrate efficient nonfullerene-based multijunction OPVs while at the same time highlighting the remaining challenges. We first demonstrate double-junction OPVs with power conversion efficiency (PCE) of 16.5%. Going a step further, we developed triple-junction OPVs with a PCE of 14.9%, the highest value reported to date for this triple-junction cells. Device simulations suggest that improving the front-cell’s carrier mobility to >5 × 10–4 cm2 V–1 s–1 is needed to boost the efficiency of double- and triple-junction OPVs. Analysis of the efficiency limit of triple-junction devices predicts that PCE values of close to 26% are possible. To achieve this, however, the optical absorption and charge transport within the subcells would need to be optimized. The work is an important step toward next-generation multijunction OPVs.